Healthcare resource utilization and costs in patients with multiple myeloma with and without skeletal-related events. (July 2020) - Ailawadhi, Sikander; Medhekar, Rohan; Princic, Nicole; Fowler, Robert; Tran, Oth; Bhowmik, Debajyoti; Panjabi, Sumeet
Aim: To compare healthcare resource use and costs between newly diagnosed multiple myeloma (NDMM) patients with and without skeletal-related events (SREs). Methods: Adults newly diagnosed with MM (1 January 2006 and 30 June 2017) with at least 12 months continuous health coverage prior to diagnosis were identified using the IBM MarketScan administrative claims. To control for baseline differences, NDMM patients with SREs were propensity score matched to NDMM patients without SREs. Outcomes included annual HRU and costs during follow-up along with number and type of SREs (SRE cohort only). Patients with SREs were stratified by number of SREs, and annual SRE-related costs were reported. Student's t test and Chi-squared test were used to compare outcomes. Results: Before matching, the 6648 patients in the SRE cohort had more comorbidities, were more likely to have MM treatment, and had higher pre-index healthcare costs than the 7458 patients in the non-SRE cohort. After matching, cohorts of 3432 patients were well balanced on baseline characteristics. Patients with SREs (vs. without SREs) had significantly higher inpatient, outpatient, and pharmacy HRU. Patients with SREs had significantly higher mean annual all-cause healthcare costs ($213, 361 vs. $94, 896, p  < 0.001) with hospitalization being the leading driver of increased costs (38.7% of total). Among 6648 patients with SREs, the mean annual SRE-related healthcare costs were $39, 603, $45, 463, and $50, 111 for patients with one, two, and three or more events, respectively. Conclusions: NDMM patients with SREs have more than twice the all-cause healthcare costs than matched patients without SREs. Costs increase with the number of SRE events.